Morphosemantic and syntactic analysis of verbs in Sindhi / Zahid Ali - Zahid, Ali (2016)
This study focuses on Sindhi Verbs in terms of morphosemantic and syntactic properties, Argument Structure, theta roles, thematic relations and the most prominent theta roles used in Sindhi. The morphosemantic properties relate to the study of morphology (morphemes) in relation to semantics (meaning). The morphosyntactic properties refer to the study of morphology and morphemes in relation to syntax. The objectives of the study are to analyse the morphosemantic and syntactic features of Sindhi verbs, to establish the Argument Structure of Sindhi verbs along with analysis of Theta-roles (θ-roles), and to investigate the prominent theta roles in Sindhi. The study applies the theoretical frameworks of Culicover (1997) and Carnie (2007) within the transformational generative grammar paradigm. It also applies Allana’s (2010) model/fact to see the standard Sindhi sentence structure in the data. Descriptive and exploratory analysis (Creswell, 2013; 2014; Neuman, 2005; Kumar, 2011) is used in the study. Data for the study come from two interviews from two native Sindhi speakers amounting to 1,679 sentences. Tree diagrams of the Sindhi sentences are drawn especially focusing on the VP. The study finds that like English it is possible to generate a V-bar from VP in Sindhi. The findings show that a slight morphological, lexical and phonological change in the form of a verb leads to a complete new form and meaning; it changes one form to other, it even changes the class of the word. Such changes also change a person, a number and a gender of a subject as well as object in a sentence. The study also finds some unusual sentential constructions like verbs with null/zero subjects and objects in the spoken Sindhi. However, such unusual constructions are grammatically accepted and theta roles are still featured in them. These constructions do not have an argument at subject or object positions in the Phonetic Form (PF), but the theta role is still featured in such construction, because the Logical Form (LF) features an argument with the verb. Most importantly, the study finds that Sindhi is a pro-drop v language where pro(s) (arguments) are normally dropped at subject or object position in the PF of the sentence. However, the deleted pro(s) or arguments are recovered through the verb inflections (INFL) and the sentence agreement (AGR) in LF of the sentence (Chomsky, 1981; Haegeman, 1994). The study finds that Sindhi has all theta roles and thematic relations which are proposed by Carnie (2007). Besides, a new argument (NP) is seen in the data which directly or indirectly contributes to other syntactic elements in sentences. However, such argument has not been discussed by Carnie (2007) in his ‘Theta Roles and Thematic Relations’. Therefore, the current study assigns it a theta role of ‘giver’ in the analysis. The study also finds that Sindhi has six prominent and frequent theta roles; agent, theme, recipient beneficiary, locative and goal. Based on the theta roles hierarchy of Levin & Hovav (2004), the hierarchy of theta roles in Sindhi is: Agent>Theme>Recipient>Locative>Beneficiary>Goal>Experiencer>Source>Instrument>Giver Therefore, future research can be into theta roles in spoken and written data from a variety of sources.